In remembrance: the life and legacy of George L. Bakris (1952–2024) - Pantelis Sarafidis; Kostas Tsioufis; Michel Burnier; Bryan Williams; Giuseppe Mancia; Thomas Weber; George S. Stergiou (Blood Pressure)
George L. Bakris passed away on 15 June 2024 at the age of 72 years. This obituary aims at honouring his life and career by describing the stages in his personal and professional pathway, presenting some of his many remarkable accomplishments, and highlighting his exceptional clinical skills, mentorship, and friendship.